The synthesis of OspD3 (ShET2) in Shigella flexneri is independent of OspC1. (1st November 2016) - Faherty, Christina S.; Wu, Tao; Morris, Carolyn R.; Grassel, Christen L.; Rasko, David A.; Harper, Jill M.; Shea-Donohue, Terez; Fasano, Alessio; Barry, Eileen M.
ABSTRACT: Shigella flexneri is a Gram-negative pathogen that invades the colonic epithelium and causes millions of cases of watery diarrhea or bacillary dysentery predominately in children under the age of 5 years in developing countries. The effector Shigella enterotoxin 2 (ShET2), or OspD3, is encoded by the sen or ospD3 gene on the virulence plasmid. Previous literature has suggested that ospD3 is in an operon downstream of the ospC1 gene, and expression of both genes is controlled by a promoter upstream of ospC1 . Since the intergenic region is 328 bases in length and contains several putative promoter regions, we hypothesized the genes are independently expressed. Here we provide data that ospD3 and ospC1 are not co-transcribed and that OspC1 is not required for OspD3/ShET2 function. Most importantly, we identified strong promoter activity in the intergenic region and demonstrate that OspD3/ShET2 can be expressed and secreted independently of OspC1. This work increases our understanding of the synthesis of a unique virulence factor and provides further insights into Shigella pathogenesis.